Revisiting the expression of BDNF and its receptors in mammalian development - Esvald, Eli-Eelika; Tuvikene, Jürgen; Kiir, Carl Sander; Avarlaid, Annela; Tamberg, Laura; Sirp, Alex; Shubina, Anastassia; Cabrera-Cabrera, Florencia; Pihlak, Arno; Koppel, Indrek; Palm, Kaia; Timmusk, Tõnis (Frontiers in Molecular Neuroscience, 2023)
Brain-derived neurotrophic factor (BDNF) promotes the survival and functioning of neurons in the central nervous system and contributes to proper functioning of many non-neural tissues. Although the regulation and role of BDNF have been extensively studied, a rigorous analysis of the expression dynamics of BDNF and its receptors TrkB and p75NTR is lacking. Here, we have analyzed more than 3,600 samples from 18 published RNA sequencing datasets, and used over 17,000 samples from GTEx, and 180 samples from BrainSpan database, to describe the expression of BDNF in the developing mammalian neural and non-neural tissues. We show evolutionarily conserved dynamics and expression patterns of BDNF mRNA and non-conserved alternative 5′ exon usage. Finally, we also show increasing BDNF protein levels during murine brain development and BDNF protein expression in several non-neural tissues. In parallel, we describe the spatiotemporal expression pattern of BDNF receptors TrkB and p75NTR in both murines and humans. Collectively, our in-depth analysis of the expression of BDNF and its receptors gives insight into the regulation and signaling of BDNF in the whole organism throughout life.